Agents of change: the Sámi Pathfinders, transforming majority-education within the cultural interface - Walsh-Knarvik, Kimble (UiT Norges arktiske universitet, 2023)
This thesis fills an academic gap about the Sámi Pathfinders, centring their stories. I examine the role of the Sámi Ofelaččat/Samiske veivisere or Sámi Pathfinders and their contribution to Indigenous education. Indigenous education is framed as part of the paradigm of Indigenous self-determination. The Sámi Pathfinders is an educational initiative whereby Norwegian pupils learn about historical and contemporary Sámi life from young Sámi. It is these young Sámi adults who assume this representative role. The motivation behind the establishment of the Sámi Pathfinders in 2004 was the recognition of the general lack of knowledge in Norwegian society about the Sámi and their rights as Indigenous People. By contributing to closing this ‘knowledge-gap’, the objective of the Sámi Pathfinder initiative is to make the Sámi culture more visible, with the long-term objective of countering discrimination and stereotypes. Providing a peer-to-peer communicative encounter, the Pathfinders primarily focus on Norwegian youth by visiting high schools covering the length and breadth of Norway. This thesis asks: How do the Sámi Pathfinders understand their role as addressing discrimination and existing stereotypical associations about the Sámi? To answer this question, I present a case study which explores the types of experiences (comments and behaviours) the Sámi Pathfinders encountered when visiting Norwegian high schools. Through semi-structured on-line interviews with five Pathfinders, this case study provided a unique opportunity to document the Pathfinders’ reflections about their experiences and accumulated knowledge. The Pathfinders’ testimonies reveal that this ‘knowledge-gap’ still exists in Norwegian schools, explaining that most schools did not prepare their pupils for their visit. Additionally, their reflections reveal that stereotypes about and discrimination towards the Sámi are ongoing concerns. With that said, I argue that the responsibility of educating the majority should not solely be placed on the Sámi ...